Use, Reuse and Valorisation : A Web App for the Italian Cultural Heritage - Fabbris, Giulia; Bertozzi, Alessandro (Mimesis Journal, 2024)
The article presents the partial results of an ongoing project whose aim is the implementation of a web application (CHIt) for the valorization of the Italian cultural heritage. This tool retrieves existing resources belonging to the Italian cultural heritage available on online platforms, reusing and integrating the gathered data and metadata according to the FAIR principles. Metadata are mapped and, if needed, formatted according to the DCMI in order to uniform consultation and ensure interoperability. The aggregated objects can be visualized and annotated thanks to the provided tools. The result is an open-access tool suitable for a varied audience.